Mono-, Di- and Tributlytin Derivatives of N-(2-Hydroxy Methyl Substituted Benzyl) Valines - Ballabh Mishra, Shasti; Chandra, Madhup (Asian Journal of Chemistry, 2012)
Mono-, di- and tributyltin derivatives of N-[2-hydroxy methyl substituted benzyl) valines have been prepared by alcoholysis reaction. The compounds were obtained as colored solids in case of mono-and dibutyltin derivatives and as dark viscous liquids in case of tributyltin derivatives. Amongst these derivatives those containing isopropoxy group were found to be hygroscopic. All these compounds were characterized by azeotrope and elemental analysis, as well as by spectral measurements.